2019
DOI: 10.1186/s13071-019-3629-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Wolbachia in field-collected Aedes aegypti mosquitoes in metropolitan Manila, Philippines

Abstract: Background Recent reports reveal the presence of Wolbachia in Ae. aegypti . Our study presents additional support for Wolbachia infection in Ae. aegypti by screening field-collected adult mosquitoes using two Wolbachia -specific molecular makers. Methods A total of 672 Ae. aegypti adult mosquitoes were collecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
131
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(144 citation statements)
references
References 39 publications
7
131
2
4
Order By: Relevance
“…Species misidentification may also cause false positives if one species harbors Wolbachia and the other does not. Both Teo et al () and Carvajal et al () used identification keys but did not confirm that samples were A. aegypti with molecular approaches. Since A. aegypti and A. albopictus are sympatric in both locations, detections of Wolbachia in A. aegypti could result from species misidentification.…”
Section: Limitations Of Studies To Datementioning
confidence: 98%
See 3 more Smart Citations
“…Species misidentification may also cause false positives if one species harbors Wolbachia and the other does not. Both Teo et al () and Carvajal et al () used identification keys but did not confirm that samples were A. aegypti with molecular approaches. Since A. aegypti and A. albopictus are sympatric in both locations, detections of Wolbachia in A. aegypti could result from species misidentification.…”
Section: Limitations Of Studies To Datementioning
confidence: 98%
“…Several species of filarial nematodes that infect A. aegypti harbor obligate Wolbachia infections from supergroups C and D (Bouchery, Lefoulon, Karadjian, Nieguitsila, & Martin, ). Both Thongsripong et al () and Carvajal et al () detected Wolbachia in A. aegypti that aligned to supergroup C. Carvajal et al () observed substantial diversity in 16S rDNA and wsp sequences, with alignments to supergroups A, B, C, D, and J. Given that Wolbachia from supergroups C, D, and J are not known to occur in Diptera, such diversity is likely explained by contamination from other sources.…”
Section: Limitations Of Studies To Datementioning
confidence: 99%
See 2 more Smart Citations
“…These studies report variable infection frequencies in populations and identify infections from several Wolbachia supergroups. Most studies found that the infections detected were closely related to or identical to the wAlbB infection that occurs natively in Aedes albopictus (Coon et al, 2016, Balaji et al, 2019, Carvajal et al, 2019, Kulkarni et al, 2019, while other studies also detected Wolbachia from supergroups that do not normally occur within Diptera (Carvajal et al, 2019, Thongsripong et al, 2018. Most evidence is limited to molecular detection but some studies established laboratory colonies and have reported maternal transmission of Wolbachia (Kulkarni et al, 2019) and the loss of infection through antibiotic treatment (Balaji et al, 2019).…”
Section: Detections Of Wolbachia In Aedes Aegyptimentioning
confidence: 99%